Ibnu Battuta, Moroccan Explorer and Contributor to Geography in Indonesia - Rudy Prasetyo; Muhammad Rico; Muhammad Riduan (Penerbit Hellow Pustaka, 2024)
Ibn Battuta was a famous Muslim traveler and jurist in the 14th century because he was known as the greatest adventurer of pre-modern times. The story of his fantastic journey made the Western world respect him as the